Fundamentals of Entrepreneurship (ENT300) : Ladies Hairlicious / Mariam Sapuan ... [et al.] - Sapuan, Mariam; Jafferi, Mira Azura; Mohd Zamzy, Nur Farahainy; Champian, Nur Saihah; Sazali, Siti Syairah (2014)
The name of the company that we agreed to choose is Ladies Hairlicious. The business is in form of partnerships, which consists of five members. Each partner contributes certain amount of cash as agreed in partnership agreement. The main activity for the business is to provide services to the ladies customers in the hair salon especially for those who wear hijab so that they can comfortably receive the sprvices from us. All partners are entitled to participate in the Business management. We have agreed that Mariam Binti Sapuan as the General Manager, Mira Azura Binti Jafferi as the Marketing Manager, Nur Farahainy Binti Mohd Zamzy as the Operation Manager, Nur Saihah Binti Champian as the Administration Manager and Siti Syairah Binti Sazali as the Financial Manager. The business will be totally own by partners of the business. The location of this business is at Jalan satok Kuching Sarawak. We likely choose this area because it more communities and we are one of the saloons that provide services for ladies only. The strategic location also might help us to earn profit and know our target markets as well.